CHINA'S WOLF WARRIOR DIPLOMACY AND THE RELATIONS WITH REPUBLIC OF KOREA (2015 - 2020) - Rizqina Ikramul Jannah Ismail; Harryanto Aryodiguno (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2022)
Abstract In recent days, the nature of the People’s Republic of China’s diplomacy has changed and it is gaining complicated responses from other countries. That famous diplomacy is called “Wolf Warrior Diplomacy”, diplomacy that is seen as ‘assertive’ and ‘threatening’ other countries when defending the country’s national interest. “Wolf Warrior Diplomacy” is a new term under the administration of President Xi Jinping however the root of it has been there since back then. This paper would discuss how this diplomacy affects the relations between China and the Republic of Korea (ROK) after ROK decides to cooperate with the United States and deploy Terminal High Altitude Area Defense (THAAD), which China believes threatened China’s national interest. The method that is used for this research is the qualitative method, by collecting data and information needed from the studies that have been made before. Based on the research that has been done, the ‘assertive’ diplomacy done by China affects how ROK faces the country and the relations between them, remembering that ROK is a country between two great power countries, China and the US. In addition, ROK has been in efforts to balance between two countries. ROK also in its ways to expand and improve its relations in other regions. Keywords: Wolf Warrior Diplomacy; coercive diplomacy; hedging strategy Abstrak Dalam beberapa hari terakhir, sifat diplomasi Republik Rakyat Tiongkok telah banyak berubah dan hal tersebut mendapatkan tanggapan yang rumit dari negara lain. Diplomasi yang terkenal itu disebut “Wolf Warrior Diplomacy (Diplomasi Prajurit Serigala)”; diplomasi tesebut dipandang ‘tegas’ dan ‘mengancam’ oleh negara lain ketika Tiongkok membela kepentingan nasional negaranya. “Wolf Warrior Diplomacy” adalah istilah baru di bawah pemerintahan Presiden Xi Jinping namun akarnya sudah ada sejak pembentukan negara Tiongkok. Artikel ini akan membahas bagaimana diplomasi ini mempengaruhi hubungan antara Tiongkok dan Republik Korea (Korea Selatan) setelah Korea Selatan memutuskan untuk bekerja sama dengan Amerika Serikat dalam menggelar Terminal High Altitude Area Defense (THAAD), yang diyakini oleh Tiongkok akan mengancam kepentingan nasional negaranya. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, yaitu dengan cara mengumpulkan data dan informasi yang dibutuhkan dari hasil penelitian-penelitian lain yang telah dilakukan sebelumnya. Berdasarkan penelitian yang telah dilakukan, diplomasi ‘asertif’ yang dilakukan oleh Tiongkok mempengaruhi bagaimana Korea Selatan menghadapi negara tersebut dan hubungan di antara mereka, mengingat Korea Selatan berada di antara dua negara dengan kekuatan yang besar, yaitu Tiongkok dan AS. Selama ini, Korea Selatan telah melakukan upaya untuk menyeimbangkan pengaruh oleh dua negara. Korea Selatan juga sedang berusaha untuk memperluas dan meningkatkan hubungannya di wilayah lain. Kata kunci: Wolf Warrior Diplomacy; diplomasi asertif; strategi hedging